Unintentional human insider threats mitigation measures in universities in Uganda - Mbabazi, Businge Phelix; Peterand, Jehopio; Muwanga – Zake, JWF (International Journal of Multidisciplinary Research and Development, 2016)
The purpose of this research paper to indentify the unintentional human insider threats and assess the various unintentional Human Insider threats mitigation measures currently used in universities in Uganda. It also intends to know the mitigation measures are actually being implemented in the universities in Uganda. The primary data was collected by using survey method. Sampling was all from ICT Staff members and the various heads of Departments who are in charge of handling institutional data. The questionnaires were distributed to 212 respondents from conveniently selected respondents from different Nine (9) Universities in Uganda. Reliability and validity of the constructs tests were carried out and all were found to be above the recommended values and Descriptive Statistics and coefficient of Variation was used to analyze these constructs. The study found out that sharing of secondary storage devices like flash discs, CD, Hard disks, Losing of Secondary storage devices like flash disks, CD, Hard and Working on a mobile device e.g. Laptop while travelling, Leaving computers unattended to were the top ranked insider threats and Usability of security tools were being implemented while Technological measures, Security training and awareness, Deterrence measures were partly implemented and Motivation measures, and Time pressure and Workload were sometimes implemented. Its recommend to further investigate on the other unintentional mitigation measure which can be used in mitigating other insider threats on institutional data security for example hackers and none human threats to information security such natural disasters and systems failures.
Keywords: Insider threats; Unintentional Human Insider threats; Mitigation Measures; Universities